(untitled) (Urdimento - Revista de Estudos em Artes Cênicas, 2024)
Based on concepts from Nogueira and Cruz, Bezelga, and Menezes, this article examines the practices of the theatre group which is based in a former silk factory in Barbacena, helping to make these listed buildings sustainable. After the factory closed government agencies took over the buildings. However, in the 1990s, the buildings were unoccupied until taken over by the Ponto de Partida Group in 1998. To restore the deactivated industrial heritage, the group involved the community of Barbacena in fund-raising and competitions, moving into Pavilion 1 in 2004. After the restoration of Pavilion 2, Bituca Music University was opened there, a tribute to the musician Milton Nascimento. Finally, the group established a community library in Pavilion 3.